(Z)-3-(4-Bromophenyl)-2-[(2-phenylcyclohex-2-en-1-yl)imino]-1,3-thiazolidin-4-one - Ooi, Chin Wei (International Union of Crystallography, 2012)
The title compound, C(21)H(19)BrN(2)OS, exists in a cis conformation with respect to the N=C bond [1.2602 (14) Å]. The cyclohexene ring adopts a distorted half-chair conformation and the C—N bond lies in an equatorial orientation. The thiazolidine ring forms dihedral angles of 53.76 (7) and 57.22 (7)° with the benzene and bromo-substituted benzene rings, respectively. The dihedral angle between the benzene and bromo-substituted benzene rings is 76.06 (7)°. In the crystal, inversion dimers linked by pairs of C—H⋯O hydrogen bonds generate R (2) (2)(14) loops. The crystal is further consolidated by weak C—H⋯π interactions.